The effects of six weeks of supplementation with multi-ingredient performance supplements and resistance training on anabolic hormones, body composition, strength, and power in resistance-trained men - Ormsbee, M. J.; Mandler, W. K.; Thomas, D. D.; Ward, E. G.; Kinsey, A. W.; Simonavice, E.; Panton, L. B.; Kim, J. (Journal of the International Society of Sports Nutrition, 2012)
Resistance training (RT) enhances muscle protein synthesis and hypertrophy while increasing strength and power. Some multi-ingredient performance supplements (MIPS) have been shown to augment the physiological improvements associated with RT. The purpose of this study was to investigate the impact of specific pre- and post-workout MIPS on body composition, muscle strength, and power in resistance-trained men participating in a periodized RT program. Methods Twenty-four ( mean +/- SE; 24.0 +/- 0.9 years; 180.5 +/- 5.8 cm; 83.7 +/- 0.5 kg) resistance-trained men completed 6 wks of periodized RT (3x/wk). Participants were assigned to one of two groups based upon maximal voluntary contraction of the quadriceps (Biodex) to lean mass (LM) ratio. Group 1 (n = 13; MIPS) consumed one serving of NO-Shotgun(R) (whey protein, casein protein, branched-chain amino acids, creatine, beta alanine, and caffeine) before each workout and one serving of NO-Synthesize(R) (whey protein, casein protein, branched-chain amino acids, creatine, and beta alanine; Vital Pharmaceuticals, Inc., Davie, FL) immediately after each workout and on non-RT days. Group 2 (n = 11; Placebo; PLA) consumed a flavor-matched isocaloric maltodextrin placebo. Serum insulin-like growth factor 1, human growth hormone , testosterone, body composition (DXA), circumferences, 1-repetition maximal strength (1RM) of the upper (chest press) and lower body (leg press), and anaerobic power (Wingate test) were assessed before and after the intervention. Statistical analysis included a 2 x 2 (group x time) ANOVA with repeated measures. Tukey LSD post hoc tests were used to examine pairwise differences. Significance was set at p < 0.05. Results There was a main time effect (p = 0.035) for testosterone to increase, but no differences between groups were observed. There were no differences in the other blood hormones. Group x time interactions were observed for LM (MIPS: PRE, 62.9 +/- 2.1 to POST, 65.7 +/- 2.0 vs. PLA: PRE, 63.5 +/- 2.3 to POST, 64.8 +/- 2.5 kg; p = 0.017). Only a main effect of time was noted for circumference measures. Both groups increased upper and lower body 1RM strength to a similar degree. MIPS significantly increased peak anaerobic power (PRE, 932.7 +/- 172.5 W vs. POST, 1119.2 +/- 183.8 W, p = 0.002) while PLA remained unchanged (PRE, 974.4 +/- 44.1 W vs. POST, 1033.7 +/- 48.6 W, p = 0.166). Conclusion Consumption of MIPS during the course of a periodized RT program facilitated training-induced improvement in LM in trained males, whereas the consumption of PLA did not. MIPS improved measures of anaerobic power while PLA did not.